Shear wave-based sound touch elastography in liver fibrosis assessment for patients with autoimmune liver diseases - Yang, Lulu (Quant Imaging Med Surg, 2021)
BACKGROUND: Shear wave-based ultrasonic elastography (USE) has been widely used for the assessment of liver fibrosis in patients with chronic liver diseases (CLD). However, diagnostic criteria and accuracy vary between different etiologies and specific elastography techniques. We aimed to evaluate the tissue stiffness measured by shear wave-based sound touch elastography (STE) in staging liver fibrosis in patients with autoimmune liver diseases (AILD). METHODS: One hundred and two AILD patients who had undergone STE liver stiffness measurements (LSMs) by using a Resona 7 ultrasound system were retrospectively studied. With the Scheuer liver fibrosis staging system as the reference, we investigated the diagnostic performance and cutoff values of STE measured liver stiffness in staging liver fibrosis through receiver operating characteristic (ROC) curve analysis. Moreover, comparisons of areas under the curve (AUCs) were made between LSMs and calculated biomarker scores, including the aspartate aminotransferase (AST)-to-platelet ratio index (APRI), and fibrosis-4 (FIB-4) index. RESULTS: Median LSMs increased with the advancing fibrosis stages with values of 6.89 kPa (1.51 m/s), 8.00 kPa (1.63 m/s), 9.60 kPa (1.79 m/s), 11.37 kPa (1.95 m/s) and 14.50 kPa (2.20 m/s), from stage 0 to stage 4 respectively. The cutoff values of STE for identifying significant fibrosis (≥ stage 2), severe fibrosis (≥ stage 3) and cirrhosis (stage 4) were 9.07 kPa (1.74 m/s), 9.97 kPa (1.82 m/s) and 10.48 kPa (1.87 m/s), respectively, with corresponding sensitivity of 79.1%, 93.3%, and 100%; specificity of 80.0%, 70.8% and 71.8%. The AUCs of LSMs in identifying fibrosis ≥ stage 2, ≥ stage 3 and stage 4 (0.82, 0.87, and 0.91, respectively) were significantly higher than that of APRI (0.67, 0.64, and 0.72, respectively) and FIB-4 (0.70, 0.68, and 0.75, respectively) (all P<0.05). CONCLUSIONS: LSM obtained by STE exhibited its good capability to evaluate liver fibrosis stages in patients with AILD. As a noninvasive modality for liver fibrosis staging, STE is superior to APRI and FIB-4 biomarker scores.